Four new species of Euphorbia sect. Pithyusa (subg. Esula, Euphorbiaceae) from SW Asia - Pahlevani, Amir H. (Phytotaxa, 2017)
Four new SW Asian species of Euphorbia subg. Esula, sect. Pithyusa are described and mapped. Euphorbia acanthoclada is known from W Afghanistan and is compared with E. acanthodes. Euphorbia boreo-baluchestanica and E. ziaratensis are found from N Baluchistan of Pakistan and are most similar to E. prolifera and E. sulphurea respectively. Euphorbia kavirensis is known from temperate desert of the interior Iran, Dasht-e Kavir, and is closely related to the Iranian E. gedrosiaca. Diagnosis, description, distribution, ecology, conservation status, image and pertinent notes, if needed, are also considered.